Bismuth improves efficacy of proton‐pump inhibitor clarithromycin, metronidazole triple Helicobacter pylori therapy despite a high prevalence of antimicrobial resistance. Issue 3 (25th April 2018) - Long, Xiaohua; Chen, Qi; Yu, Lou; Liang, Xiao; Liu, Wenzhong; Lu, Hong
Abstract: Background: Helicobacter pylori ( H. pylori ) eradication has become increasingly difficult especially for penicillin allergy patients. Aims: To evaluate the efficacy of adding bismuth or high‐dose metronidazole to an H. pylori eradication regimen containing a proton‐pump inhibitor, clarithromycin, and metronidazole in patients allergic to penicillin. Methods: Pilot study in which penicillin‐allergic, treatment‐naive subjects were randomized (1:1) to 14‐day esomeprazole (20 mg q12h), clarithromycin (500 mg q12h), and high dose of metronidazole (400 mg q6h) with (BECM group) or without (ECM group) bismuth (600 mg q12h). Eradication was confirmed by 13 C‐urea breath test 6 weeks after therapy. Antimicrobial susceptibility was assessed by the agar dilution method. Adverse events were recorded. Results: Sixty‐six subjects were randomized, four were lost to follow‐up and eight violated the protocol. The eradication rates were 63.6% (95% CI: 47.2%‐80.0%) for ECM vs 84.8% (95% CI 72.6%‐97.1%) ( p  = .049) for BECM by intention‐to‐treat, 67.7% (95% CI 51.3%‐84.2%) vs 90.3% (95% CI 79.9%‐100%) ( p  = .029) by modified ITT, and 70% (95% CI 53.6%‐86.4%) vs 96% (95% CI 88.3%‐100%) ( P  = .033) by per‐protocol. Metronidazole, clarithromycin, and dual‐resistant rates were 74.2%, 24.2%, and 18.2%, respectively. The cure rates were significantly improved by the addition of bismuth for both clarithromycin‐resistant isolates (100% vs 25%, P  = .024) and metronidazole‐resistant isolates (94.7% vs 63.6%, P  = .043). Adverse events were reported by 45.5% of subjects in ECM group and 48.5% in the BECM group ( P  = .805). Conclusions: This prospective trial demonstrated that while high‐dose metronidazole could not completely overcome metronidazole resistance, bismuth was additive and improved the overall cure rates by 21%‐26%.